(f+g)(x) = 8x+2
(f-g)(x) = 4x-6
Step-by-step explanation:
Given

we have to find
<u>a. (f+g)(x)</u>

<u>b. (f-g)(x)</u>

Hence,
(f+g)(x) = 8x+2
(f-g)(x) = 4x-6
Keywords: Functions, Operations on Functions
Learn more about functions at:
#LearnwithBrainly
Answer:
18+2x
Step-by-step explanation:
6-4(2x-3)+10x
6-8x+12+10x multiply 2x-3 by -4
18+2x combine like terms
B is the answer B is the answer B is the answer B is the answer
Answer:
i believe its C
Step-by-step explanation:
Answer: 75%
Step-by-step explanation:
Height given :
69, 62, 73, 67, 63, 65, 73, 71, 70, 66, 59, 75
The total number of height given = 12
The height less than 73 are 69 , 62, 67 ,63 , 65 , 71 , 70 , 66 , 59
The total number of heights less than 73 = 9
Therefore : the percentage of these students who are shorter than 73 inches = total number of students shorter than 73/ total number of height x 100
= 9/12 x 100
= 75%